An Efficient Method for the Synthesis of N‐uracil‐4‐oxo‐thiazolidines without Catalyst. (9th July 2019) - Mohamed, Asmaa H.; Shaker, Raafat M.
Abstract : We have developed highly efficient, one‐pot three component reaction of 5‐amino‐uracil and aromatic aldehydes with thioglycolic acid for the synthesis of N‐uracil‐thiazolidinones in excellent yields. The same products were also prepared by the reaction of Schiff bases of 5‐amino‐uracil with thioglycolic acid. In addition, benzylation of thiazolidinone derivatives and Schiff bases by using benzyl chloride was investigated. The results obtained from elemental microanalysis and different spectral data are in agreement with the assigned structures. Abstract :